Diagnostic Performance of the New Version (v2.0) of GenoType MTBDRsl Assay for Detection of Resistance to Fluoroquinolones and Second-Line Injectable Drugs: a Multicenter Study - Tagliani, Elisa (J Clin Microbiol, 2015)
Resistance to fluoroquinolones (FLQ) and second-line injectable drugs (SLID) is steadily increasing, especially in eastern European countries, posing a serious threat to effective tuberculosis (TB) infection control and adequate patient management. The availability of rapid molecular tests for the detection of extensively drug-resistant TB (XDR-TB) is critical in areas with high rates of multidrug-resistant TB (MDR-TB) and XDR-TB and limited conventional drug susceptibility testing (DST) capacity. We conducted a multicenter study to evaluate the performance of the new version (v2.0) of the Genotype MTBDRsl assay compared to phenotypic DST and sequencing on a panel of 228 Mycobacterium tuberculosis isolates and 231 smear-positive clinical specimens. The inclusion of probes for the detection of mutations in the eis promoter region in the MTBDRsl v2.0 test resulted in a higher sensitivity for detection of kanamycin resistance for both direct and indirect testing (96% and 95.4%, respectively) than that seen with the original version of the assay, whereas the test sensitivities for detection of FLQ resistance remained unchanged (93% and 83.6% for direct and indirect testing, respectively). Moreover, MTBDRsl v2.0 showed better performance characteristics than v1.0 for the detection of XDR-TB, with high specificity and sensitivities of 81.8% and 80.4% for direct and indirect testing, respectively. MTBDRsl v2.0 thus represents a reliable test for the rapid detection of resistance to second-line drugs and a useful screening tool to guide the initiation of appropriate MDR-TB treatment.